28.9k views
4 votes
-3x − y = 5
10x + 9y = 6

2 Answers

5 votes

Answer:

x=-3, y=4. (-3, 4).

Explanation:

-3x-y=5

10x+9y=6

---------------

y=-3x-5

10x+9(-3x-5)=6

10x-27x-45=6

-17x-45=6

-17x=6+45

-17x=51

x=51/-17

x=-3

y=-3(-3)-5

y=9-5

y=4

User Kscottz
by
5.1k points
1 vote

Answer:

(- 3, 4 )

Explanation:

Given the 2 equations

- 3x - y = 5 → (1)

10x + 9y = 6 → (2)

Rearrange (1) expressing y in terms of x by adding 3x to both sides

- y = 5 + 3x ( multiply through by - 1 )

y = - 5 - 3x → (3)

Substitute y = - 5 - 3x into (2)

10x + 9(- 5 - 3x) = 6 ← distribute and simplify left side

10x - 45 - 27x = 6

- 17x - 45 = 6 ( add 45 to both sides )

- 17x = 51 ( divide both sides by - 17 )

x = - 3

Substitute x = - 3 into (3) for corresponding value of y

y = - 5 - 3(- 3) = - 5 + 9 = 4

Solution is (- 3, 4 )

User Jim Munro
by
5.0k points